Dato' Sri Ibrahim Ahmad the new chairman for UMP Board of Directors - Siti Sarah, Mohamad Rajimi (2018)
Pekan, 5 January - Dato’ Sri Ibrahim Ahmad, 61 has been appointed the new chairman of UMP Board of Directors, for three years starting from 1 January 2018 until 31 December 2020. The appointment was made by the Minister of Higher Education Malaysia, Datuk Seri Idris Jusoh in accordance with the provisions of Section 17 (1) (a) of the University Constitution. Dato’ Sri Ibrahim Ahmad is taking over the post from Dato’ Sri Mohd. Hilmey Mohd Taib who has served as the chairman for 11 years since 1 September 2006 until 31 August 2017.